Odpowiedzi

2010-02-12T11:08:31+01:00
K=(-2)³×(2/5)°+(⅓)²×3-√9×(⅓)²= -8×1 +1/9 ×3 - 3×1/9=

-8+⅓ -⅓ = -8

l=pierw z 16+9 -⅓×(√3)² = 5-⅓×3=5-1=4
k÷l=-8÷4=-2

k=(39-15)÷2³ +(3×2²)÷(3-7) = 24÷8 + 12÷4= 3 +3 =6

l=3/2 - ⅕× 5/13 -(3-5)×¾= 3/2-1/13 -(-2)×3/4= 3/2 -1/13 +3/2= 6/2 -1/13=3-1/13=2 i 12/13
k jest wieksze

5½- [1,2× 7/12 -0,8/(-2)²]÷(-1/3) =
5½ -[12/10 ×7/12 -(8/10÷4)]×(-3)=
11/2- [7/10 -2/10]×(-3)=
11/2- 5/10×(-3)=
11/2 +15/10=11/2 +3/2= 14/2=7
30% z 7=3/10×2=21/10=2,1

Najlepsza Odpowiedź!
2010-02-12T11:22:49+01:00
1.
k=-8*1+1/9*3-3*1/9=-8+⅓-⅓=-8
l=5-⅓*3=5-1=4
k/l=-8/4=-2

2.k=24:8+12/-4=3+(-3)=0
l=3/2-1/13+2*¾=3/2-1/13+3/2=-1/13
0>-1/13
k>l

3.
...=11/2-[12/10*7/12-(8/10//4]*(-3)=11/2-[7/10-8/10*1/4)]*(-3)=
=11/2-[7/10-2/10]*(-3)=11/2-5/10*(-3)=11/2+15/10=
=11/2+3/2=14/2=7

30%*7=3/10*7=21/10=2.1